Relative Consumption, Optimal Taxation and Public Provision of Private Goods - Tobias Koenig; Tobias Lausen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2013)
This paper shows that public provision of private goods may be justified on pure efficiency grounds in an environment where individuals have relative consumption concerns. By providing private goods, governments directly intervene in the consumption structure, thereby having an instrument to correct for the excessive consumption of positional goods. We identify sufficient conditions where public provision of private goods is always part of the optimal policy mix, even when consumption taxes are available. In fact, with public provision of private goods, there are cases where the first-best allocation can be achieved, and (linear) consumption taxes can be redundant.
Keywords: H42; D62; 330; Public Provision; Social Preferences; Status; Optimal Taxation